A prominent domestic engineer of railroads - Melnikov Pavel Petrovich - A. Yu. Bilyk; M. R. Pliushch (History of science and technology, 2013)
The vital and creative way of prominent domestic scientist, engineer of railroads, first Minister of roads of the Russian empire P.P. Melnikova (1804-1880), who was the original designer of the railway system of the country is discussed in the paper.